Proof-of-concept single-arm trial of bevacizumab therapy for brain arteriovenous malformation. Issue 1 (17th March 2021) - Muster, Rachel; Ko, Nerissa; Smith, Wade; Su, Hua; Dickey, Melissa A; Nelson, Jeffrey; McCulloch, Charles E; Sneed, Patricia K; Clarke, Jennifer L; Saloner, David A; Eisenmenger, Laura; Kim, Helen; et al.
Abstract : Brain arteriovenous malformations (bAVMs) are relatively rare, although their potential for secondary intracranial haemorrhage (ICH) makes their diagnosis and management essential to the community. Currently, invasive therapies (surgical resection, stereotactic radiosurgery and endovascular embolisation) are the only interventions that offer a reduction in ICH risk. There is no designated medical therapy for bAVM, although there is growing animal and human evidence supporting a role for bevacizumab to reduce the size of AVMs. In this single-arm pilot study, two patients with large bAVMs (deemed unresectable by an interdisciplinary team) received bevacizumab 5 mg/kg every 2 weeks for 12 weeks. Due to limitations of external funding, the intended sample size of 10 participants was not reached. Primary outcome measure was change in bAVM volume from baseline at 26 and 52 weeks. No change in bAVM volume was observed 26 or 52 weeks after bevacizumab treatment. No clinically important adverse events were observed during the 52-week study period. There were no observed instances of ICH. Sera vascular endothelial growth factor levels were reduced at 26 weeks and returned to baseline at 52 weeks. This pilot study is the first to test bevacizumab for patients with bAVMs. Bevacizumab therapy was well tolerated in both subjects. No radiographic changes were observed over the 52-week study period. Subsequent larger clinical trials are in order to assess for dose-dependent efficacy and rarer adverse drug effects. Trial registration number: NCT02314377 .